Repercussions in Educational Robotic of the information and communications technology to the instructional didactic servo technology and paintings in their steps fractals (2016)
ABSTRACT: This project shows the significant learning achievement using different director of information according to the logical and visual model of multiple learning styles with multimedia (EMMA) For this investigation the educative servo technology was being used for the first time in this scientific work for geometric activities. The uniform rectilinear movement and the uniform curvilinear movement were the developed activities.